High transient stress in the lower crust: Evidence from dry pseudotachylytes in granulites, Lofoten Archipelago, northern Norway - Dunkel, Kristina G.; Zhong, Xin; Arnestad, Paal Ferdinand; Valen, Lars Vesterager; Jamtveit, Bjørn (2021)
Seismic activity below the standard seismogenic zone is difficult to investigate because the geological records of such earthquakes, pseudotachylytes, are typically reacted and/or deformed. Here, we describe unusually pristine pseudotachylytes in lower-crustal granulites from the Lofoten Archipelago, northern Norway. The pseudotachylytes have essentially the same mineralogical composition as their host (mainly plagioclase, alkali feldspar, orthopyroxene) and contain microstructures indicative of rapid cooling, i.e., feldspar microlites and spherulites and "cauliflower" garnets. Mylonites are absent, both in the wall rocks and among the pseudotachylyte clasts. The absence of features recording precursory ductile deformation rules out several commonly invoked mechanisms for triggering earthquakes in the lower crust, including thermal runaway, plastic instabilities, and downward propagation of seismic slip from the brittle to the ductile part of a fault. The anhydrous mineralogy of host and pseudotachylytes excludes dehydration-induced embrittlement. In the absence of such weakening mechanisms, stress levels in the lower crust must have been transiently high.